Voice Handicap Index (VHI) in Persian Speaking Parkinson\'s Disease Patients - Fatemeh Madjdinasab; Sakine Cheraghi; Negin Moradi; Siamak Karkheiran; Mohammad Kamali (University of Social Welfare & Rehabilitation Sciences, 2014)
Objectives: “Voice” is affected more and sooner than other speech subsystems in Parkinson's Disease (PD). Voice Handicap Index (VHI) is the most applicable subjective self-rating questionnaire in VD patients. The aim of this study was the investigation of Voice handicap in Iranian PD patients. Methods & Materials: This cross-sectional, analytical and non-interventional study was done on 50 (35 males, 15 females) patients who reported a VD related to their PD. They were selected from thepatients referring to movement disorders’ clinic in Rasool Akram Hospital affiliated withTehran University of medical sciences, through easy sampling. VHI total score (VHIT) and its domains (functional-VHIF, Emotional VHIE, Physical VHIP) was assessed in all of participants and by gender segregation. Results: 83% of patients reported voice handicap. There wasn't any difference between VHIT and its mentioned 3 domains in both sexes. There is positive correlation between VHIT, VHIE and VHIF with age. VHIT and VHIF had a positive relationship with disease duration (DD). The males VHIT and the mentioned domains had positive correlations with DD. Conclusion: Most of Iranian PD patients feel handicap due to voice disorder caused by PD and their quality of life was affected by voice impairment. Increase in age and disease duration caused more voice disorder and reduced quality of life especially patients feel more handicaps in functional domain (VHIF). In addition, the males feel more handicap than females when DD develops.